A270 AMPULLARY MORPHOLOGY PREDICTS SUCCESS AND POST-PROCEDURE COMPLICATIONS IN PRIMARY NEEDLE-KNIFE FISTULOTOMY FOR BILIARY CANNULATION IN ERCP: RESULTS OF A PROSPECTIVE CASE SERIES. (26th February 2020) - Hew, S; Taylor, C; Hookey, L; Bechara, R
Abstract: Background: Biliary cannulation is often the most challenging component of successful ERCP. Needle-knife fistulotomy (NKF) involves incising directly into the intra-duodenal portion of the bile duct, away from the native orifice, to achieve direct biliary access. This technique is usually performed when standard cannulation is unsuccessful, however recently, has been shown by our group to be a potentially effective and safe method to achieve biliary access as the primary approach. It has also been demonstrated that ampullary morphology influences cannulation success. Aims: This study aims to assess the impact of ampullary morphology on the success and complications of NKF. Methods: A retrospective visual analysis was performed of the ampullary morphology collected prospectively as part of our original NKF study (NCT03698266). Endoscopic videos and photos were reviewed to classify the ampulla into one of four types, as per a validated classification system. Ampullas were either Type 1 (regular), Type 2 (small), Type 3 (protruding or pendulous) or Type 4 (creased or ridged). Outcomes examined included: time to cannulation, proceduralist-perceived difficulty and complications. Results: Of the 71 patients enrolled in the NKF study, 66 had video or photographs of the ampulla to facilitate classification. There were 35 (52%) Type 1 ampullas, 16 (24%) Type 2 and 14 (21%) Type 3 and one (1%) Type 4 ampullas. 65 out of the 66 (98.4%) patients had successful biliary access after primary NKF. The mean time to cannulation in all patients was 5.3 minutes (range 0.25–27 minutes). There were 3 cases of post-ERCP pancreatitis (PEP) (4.5%) and 3 cases of post-ERCP bleeding (4.5%). Compared to Type 1 ampullas, there was a no significant increase in time to cannulation in Type 2 and Type 3 ampullas using NKF (Type 1 4.7 vs. Type 2 7.1 vs. Type 3 6.4 minutes, p = NS). Only one patient with a Type 2 ampulla was rated as 'low difficulty' by the proceduralist performing NKF. Nevertheless, successful NKF was achieved in 15 out of 16 Type 2 ampullas (93.8%). There was 100% success rate in biliary access for Type 3 ampullas, previously shown to more challenging using conventional cannulation techniques. All cases of PEP occurred in patients with Type 2 ampullas. Conclusions: As with the impact on conventional cannulation, ampullary morphology may influence outcomes of NKF. It appears that small, Type 2 ampullas with a short intra-duodenal segment makes NKF more challenging and may be associated with a higher rate of PEP. Unlike conventional cannulation, Type 3 ampullas are similar to Type 1 ampullas in ease of NKF access. Funding Agencies: None